2015
DOI: 10.1007/s00253-015-6500-x
|View full text |Cite
|
Sign up to set email alerts
|

The glyoxylate shunt is essential for CO2-requiring oligotrophic growth of Rhodococcus erythropolis N9T-4

Abstract: Rhodococcus erythropolis N9T-4 shows extremely oligotrophic growth requiring atmospheric CO2 and forms its colonies on an inorganic basal medium (BM) without any additional carbon source. Screening of a random mutation library constructed by a unique genome deletion method that we established indicated that the aceA, aceB, and pckG genes encoding isocitrate lyase, malate synthase, and phosphoenolpyruvate carboxykinase, respectively, were requisite for survival on BM plates. The aceA- and aceB deletion mutants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…At the very least, we can say that the formaldehyde metabolism seems not to be involved in the adhX-dependent HYGO phenotype, since we could not detect formaldehyde dismutase activity of AdhX (data not shown). Recently, using a random mutagenesis strategy for N9T-4 cells, it was revealed that (i) the glyoxylate shunt and gluconeogenesis are essential for the oligotrophic growth of N9T-4 cells and (ii) N9T-4 has a functional bypass route on the TCA cycle connecting α-ketoglutarate with succinate via succinic semialdehyde [11]. It was suggested that such carbon metabolic pathways are involved in the carbon and energy conservation mechanisms needed for oligotrophy, although the fundamental CO 2 -fixation mechanism in N9T-4 -including the roles of MDH and nFADH -is still unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the very least, we can say that the formaldehyde metabolism seems not to be involved in the adhX-dependent HYGO phenotype, since we could not detect formaldehyde dismutase activity of AdhX (data not shown). Recently, using a random mutagenesis strategy for N9T-4 cells, it was revealed that (i) the glyoxylate shunt and gluconeogenesis are essential for the oligotrophic growth of N9T-4 cells and (ii) N9T-4 has a functional bypass route on the TCA cycle connecting α-ketoglutarate with succinate via succinic semialdehyde [11]. It was suggested that such carbon metabolic pathways are involved in the carbon and energy conservation mechanisms needed for oligotrophy, although the fundamental CO 2 -fixation mechanism in N9T-4 -including the roles of MDH and nFADH -is still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…This bacterium requires CO 2 for its oligotrophic growth but shows none of the known activities and none of the genes for the key enzymes in microbial CO 2 fixation pathways identified to date, suggesting that it has a unique carbon metabolism and CO 2 fixation system [10]. Using a random mutagenesis strategy for N9T-4 cells, Yano et al [11] revealed that (i) the glyoxylate shunt and gluconeogenesis are essential for the oligotrophic growth of N9T-4 and (ii) N9T-4 has a functional bypass route on the tricarboxylic acid (TCA) cycle connecting α-ketoglutarate with succinate via succinic semialdehyde, suggesting that such carbon metabolic pathways are involved in the carbon and energy conservation mechanisms needed for oligotrophy. However, the core CO 2 -fixation mechanism of this strain under oligotrophic conditions is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Using a random mutagenesis strategy for N9T-4 cells, we revealed that the glyoxylate shunt and gluconeogenesis are essential for its oligotrophic growth. 7) Furthermore, we found that N9T-4 has a functional bypass route on the TCA cycle connecting α-ketoglutarate with succinate via succinic semialdehyde. 7) We suggest that the carbon metabolic pathways described above are involved in the carbon and energy conservation mechanisms needed for oligotrophy.…”
mentioning
confidence: 85%
“…7) Furthermore, we found that N9T-4 has a functional bypass route on the TCA cycle connecting α-ketoglutarate with succinate via succinic semialdehyde. 7) We suggest that the carbon metabolic pathways described above are involved in the carbon and energy conservation mechanisms needed for oligotrophy. From the perspective of application, we believe that this oligotrophic feature of N9T-4 would provide good cost performance for the production of useful compounds such as biofuels, since the cells can be cultivated under the very low nutrient conditions described above.…”
mentioning
confidence: 85%
See 1 more Smart Citation